2015
DOI: 10.1002/dev.21290
|View full text |Cite
|
Sign up to set email alerts
|

Gonadectomy before puberty increases the number of neurons and glia in the medial prefrontal cortex of female, but not male, rats

Abstract: The human prefrontal cortex, important for executive functions, loses gray matter throughout the adolescent period. In rats, our laboratory demonstrated that a loss of neurons between adolescence and adulthood partially underlies the loss of volume, and this loss is greater in females than males. Here, we examine whether being deprived of gonadal hormones before puberty through adulthood influences the number of neurons in the medial prefrontal cortex (mPFC). Prior to puberty, the testes or ovaries were remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 40 publications
(68 reference statements)
4
74
0
Order By: Relevance
“…Here, we examine the trajectory of the neuronal losses took place between P35 and P45. Ovariectomy before puberty at P20 prevented this neuronal loss in females compared to intact females by adulthood (Koss et al, 2015), suggesting that ovarian hormones may play a role in the pruning of neurons. In the present study, neuronal losses coincided with pubertal onset provides more support for a role of ovarian hormones at puberty in the development of the PFC in adolescent females.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Here, we examine the trajectory of the neuronal losses took place between P35 and P45. Ovariectomy before puberty at P20 prevented this neuronal loss in females compared to intact females by adulthood (Koss et al, 2015), suggesting that ovarian hormones may play a role in the pruning of neurons. In the present study, neuronal losses coincided with pubertal onset provides more support for a role of ovarian hormones at puberty in the development of the PFC in adolescent females.…”
Section: Discussionmentioning
confidence: 96%
“…In the rat mPFC, the number of neurons decreases between adolescence and adulthood with neuronal loss being considerably greater in females (Markham et al, 2007). There is further evidence that in females, the actions of hormones secreted after puberty lead to this decrease in mPFC neuron number, as ovariectomy before puberty prevents this loss when neuron number is assessed in adulthood (Koss et al, 2015). This is similar to findings in the primary visual cortex where ovarian hormones after puberty were found to play a role in neuronal pruning (Nuñez et al, 2002).…”
mentioning
confidence: 99%
“…For example, there is a loss of volume during adolescence, which is at least partially attributable to a loss of neurons, which is more significant in females [41]. Moreover, in adult rats, medial frontal pyramidal neurons are more complex, and the synaptic density is higher in males [33].…”
Section: Discussionmentioning
confidence: 99%
“…This decline in humans and rats coincides with the average onset of puberty, suggesting a hormonal role in cortical restructuring. To support this hypothesis, Koss et al (2015)) found that pre-pubertal gonadectomy did not have an effect in males, but prevented the neuron and glial loss in the mPFC in female rats, suggesting that ovarian hormones are involved in the loss of cortical neurons during adolescence. Given that gonadal hormones appear to be involved in the cortical restructuring that occurs during adolescence, it is plausible that endocrine disruptors, such as BPA, could alter normal development.…”
Section: Introductionmentioning
confidence: 99%